Geotechnical Behaviour of Frozen Mine Backfills - Han, Fa Sen (2011)
This thesis presents the results of an investigation of factors which influence the geotechnical properties of frozen mine backfill (FMB). FMB has extensive application potential for mining in permafrost areas. The uniaxial compressive strength (UCS) of hardened backfill is often used to evaluate mine backfill stability. However, the deformation behaviour and stiffness of the FMB are also key design properties of interest. In this thesis, uniaxial compressive tests were conducted on FTB and FCPB samples. Information about the geotechnical properties of FMB is obtained. The effects of FMB mix components and vertical compression pressure on the geotechnical properties of FMB are discussed and summarized. An optimum total water content of 25%-35% is found in which the strength and the modulus of elasticity of the FTB are 1.4-3.2 MPa and 35-58 MPa, respectively. It is observed that a small amount (3-6%) of cement can significantly change the geotechnical properties of FTB.